An In Vitro Model for the Development of Mature Bone Containing an Osteocyte Network. Issue 2 (22nd December 2017) - Iordachescu, Alexandra; Amin, Harsh D.; Rankin, Sara M.; Williams, Richard L.; Yapp, Clarence; Bannerman, Alistair; Pacureanu, Alexandra; Addison, Owen; Hulley, Philippa A.; Grover, Liam M.
Abstract: Bone is a dynamic tissue that remodels continuously in response to local mechanical and chemical stimuli. This process can also result in maladaptive ectopic bone in response to injury, yet pathological differences at the molecular and structural levels are poorly understood. A number of in vivo models exist but can often be too complex to allow isolation of factors which may stimulate disease progression. A self‐structuring model of bone formation is presented using a fibrin gel cast between two calcium phosphate ceramic anchors. Femoral periosteal cells, seeded into these structures, deposit an ordered matrix that closely resembles mature bone in terms of chemistry (collagen:mineral ratio) and structure, which is adapted over a period of one year in culture. Raman spectroscopy and X‐ray diffraction confirm that the mineral is hydroxyapatite associated with collagen. Second‐harmonic imaging demonstrates that collagen is organized similarly to mature mouse femora. Remarkably, cells differentiated to the osteocyte phase are linked by canaliculi (as demonstrated with nano‐computed tomography) and remained viable over the full year of culture. It is demonstrated that novel drugs can prevent ossification in constructs. This model can be employed to study bone formation in an effort to encourage or prevent ossification in a range of pathologies. Abstract : This unique biosystem allows the growth of tissue with similarities to mature bone. Its structure allows the maintenance of an osteocytic phenotype for one year in culture, a major advance on the current state of the art. The utility of this system is demonstrated by administering antiosteogenic compounds. This system will be an excellent tool for studying both aberrant and normal processes of bone formation.